Climate smart management practices add value to mature organic almond production system - Krach, Raquel J.; Daley, Cynthia A.; Liles, Garrett C. (Frontiers in Sustainable Food Systems, 2025)
This study assessed the impact of compost applications and multispecies cover crops on almond production and soil health with the working hypothesis that one or both practices would improve soil structure and fertility and therefore increase the overall productivity of the orchard. Treatments were applied to a 17-year-old organic almond orchard in a randomized complete block design for three consecutive years. Treatments included: (1) Fall-applied compost (COMP), (2) Fall-seeded multispecies cover crop (MSCC), (3) both compost and cover crop combined (COMP + MSCC), and (4) a non-treated control (CONT). Soil samples were collected in the fall of year one, before treatments were applied, and again in the fall of year three. Samples were analyzed for physical, chemical, and biological characteristics at the Center for Regenerative Agriculture & Resilient Systems’ (CRARS) Regenerative Agriculture Demonstration Lab and at a commercial soil lab. Almonds were harvested by row to determine yield within each plot and kernels were analyzed for nutrient content after the third growing season. Understory forage was collected in the spring of year three and analyzed for quality and dry matter production. After 3 years, soil in all treatment plots (COMP, MSCC, and COMP + MSCC) had higher quantities of soil organic matter (SOM), and therefore carbon, nitrogen, and other nutrients, as compared to CONT, with compost increasing SOM content more than the cover crop treatment (p < 0.05). Microbial biomass was higher in COMP + MSCC plots compared to CONT plots (p < 0.05) and microbial activity (soil respiration rate and % microbially active carbon) was higher in the COMP plots compared to CONT plots (p < 0.05). Understory forage biomass and nutritional quality were significantly higher in the MSCC and COMP + MSCC treatment plots compared with plots without cover crops (p < 0.05). This is an important benefit since orchard understory grazing with sheep is an important component of this farm’s normal operation. Finally, almond yields and kernel nutrient densities were significantly higher in treatment plots compared to control plots (p < 0.05). Collectively, these results demonstrate the multiple benefits of these regenerative/climate-smart practices in an organic orchard system.